Electronic-Topological Study of the Structure-Activity Relationships in a Series of Steroids with Mineralocorticoid Binding Affinity - Kandemirli, Fatma; Tokay, Nesrin; Shvets, Nataly M.; Dimoglo, Anatoly S. (Arzneimittelforschung, 2003)
Conformational analysis and quantum chemical calculations were carried out using molecular mechanics (MMP2) and semi-empirical quantum chemistry (CNDO/2) methods for 51 steroid homologues belonging to a series of 17-spirolactones. Matrices called Electronic-Topological Matrices of Conjunction (ETMCs) were formed using data obtained from quantum chemical calculations. A structural fragment of activity was identified in the series of steroids. As seen from the fragment’s properties, active compounds are characterized by the presence of two atoms of oxygen, O1 and O3, which are situated at a distance of 13.5 A˚ and possess high negative charges (–0.29 to –0.31 e¯).
Keywords: Mineralocorticoids, electronic-topological method, structure-activity relationship,; 17-Spirolactones